2022
DOI: 10.1002/jcsm.13158
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based assessment of body composition and liver tumour burden for survival modelling in advanced colorectal cancer

Abstract: Background Personalized therapy planning remains a significant challenge in advanced colorectal cancer care, despite extensive research on prognostic and predictive markers. A strong correlation of sarcopenia or overall body composition and survival has been described. Here, we explore whether automated assessment of body composition and liver metastases from standard of care CT images can add to clinical parameters in personalized survival risk prognostication. Methods We retrospectively analysed clinical ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In 5,395 patients, body composition was automatically assessed from abdominal CT images taken before treatment initiation. 21,22 In total, we included 350 parameters in our analysis, consisting of different modalities and both patient- and tumor-specific parameters (see methods for a detailed description of the parameters).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 5,395 patients, body composition was automatically assessed from abdominal CT images taken before treatment initiation. 21,22 In total, we included 350 parameters in our analysis, consisting of different modalities and both patient- and tumor-specific parameters (see methods for a detailed description of the parameters).…”
Section: Resultsmentioning
confidence: 99%
“…In the medical domain, xAI has previously been applied to validate the model performance or assess feature importance across cohorts. 17,22,38 Few studies have made use of patient-wise xAI explanations. 17 Here, we built on xAI to contextualize complex multimodal patient data and systematically reveal the underlying mechanisms driving a patient’s disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the trajectory of BMI is a critical independent prognostic factor, where it is a parameter containing longitudinal information of multiple compositions. Adiposity-related [ 17 ] and muscle-related indexes such as SMVI, muscle-to-bone ratio, or skeletal muscle radiodensity [ 16 , 18 ] are also essential prognostic factors, yet frequent assessments are limited since these parameters are products of occasional CT imaging studies that depend on cancer treatment progress, patient’s medical condition, health insurance, etc. Thus, synergizing CT-driven information and BMI data will promote the future clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the medical application of artificial intelligence (AI) using machine and deep learning algorithms has increased, enabling the resolution of medical problems with ease of use, robustness, and precision [15]. Moreover, studies have demonstrated that automated CT imaging evaluations using deep learning models are feasible for extracting complicated body composition parameters, and the prognostic effects of these measurements on mortality in CRC have been confirmed [16][17][18]. Although previous automated body profile evaluations have partially fulfilled the gap for clinical application, the evaluation of adiposity and muscularity is limited to one time point, and thus, not considered alternatively during various treatment or interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Liver metastasis is a significant determinant of the prognosis for colorectal cancer (CRC) patients, often resulting in organ failure and a high mortality rate ( 1 , 2 ). Over 80% of patients diagnosed with colorectal liver metastases (CRLM) are not suitable candidates for surgical removal ( 3 ). Typically, patients with unresectable CRLM administered systemic FOLFOX (folinic acid, 5-fluorouracil, oxaliplatin) or FOLFIRI (folinic acid, 5-fluorouracil, and irinotecan) treatment, either with or without bevacizumab or cetuximab as first-line therapy ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%